Base And Precious Metal Resources In Seafloor Polymetallic Sulfides - Mark D. Hannington (International Marine Minerals Society, 1994)
Seafloor polymetallic sulfides have been found in diverse volcanic and tectonic settings on the ocean floor at water depths ranging from 3700 meters to <1500 meters. More than 100 occurrences of hydrothermal mineralization have been documented (including Fe-oxide deposits, Mn-crusts, metalliferous sediments, and massive sulfides), but high-temperature hydrothermal activity and large accumulations of polymetallic sulfides are known at fewer than 20 different sites. Chemical analyses of samples from these deposits indicate that they contain important concentrations of Cu, Zn, Ag, and Au, comparable to those of massive sulfide deposits on land. However, the lack of sufficient data concerning the distribution, size, and bulk composition of seafloor deposits precludes a meaningful assessment of their resource potential.